Improving EU Fund Absorption in Romania: A Case Study on Beneficiary Insights - State, Cristina; Wang, Jianbo; Dinicu, Andrei-Edward; Rizoiu, Leonard-Alin (European Journal of Sustainable Development, 2025)
Funding has always been and will remain one of the essential challenges that any entrepreneur must overcome and find sustainable and efficient solutions for in the medium and long term. The same principle applies to the public sector, which needs investments for the production of goods, the provision of services, and infrastructure. European non-reimbursable funds represent important sources through which both the public and private sectors can develop more quickly and efficiently. However, the absorption of funds is a slow process, with Romania not fully implementing the total amounts made available by the European Union. Based on these ideas, we initiated our research, the aim of which is to identify methods to improve the absorption of European non-reimbursable funds. For this purpose, the research includes a questionnaire that was distributed via crowdsourcing and completed by 575 respondents. Subsequently, the recorded responses were processed econometrically using IBM SPSS20, and the analysis techniques used included quantitative data analysis, descriptive statistics methods, multiple response analysis, cross-data analysis, and the ?2 contingency coefficient. Five research hypotheses were formulated, including three main and two secondary ones. Through these, we analyzed the perspective of potential beneficiaries regarding their relationship with the representatives of the relevant ministry, the absorption process, the difficulties encountered, and their perception of the way the Union distributes funds to member countries. In the end, all five research hypotheses were validated. Keywords: European Funds, Investments, Project Management, IBM SPSS20, Organizational Communication